The Development of an Interactive Learning Website Based on Google Sites on Photosynthesis Material - Rasyid, Magfirah; Yusuf, Yusmar; Saibi, Ningsi; Tala, WD. Syarni; Salewangeng, Aswal (JURNAL BIOEDUKASI, 2025)
Learning media can help improve understanding and facilitate the interpretation of learning materials. They also play a role in generating enthusiasm and interest in learning among students. This research project aims to develop learning media websites based on Google sites and to test the feasibility of creating valid and practical interactive learning websites using this platform. The interactive learning websites produced in this study have been validated to ensure they are valid and practical, and will be used in plant physiology courses on photosynthesis. The research and development follows the 1974 Thiagarajan model of 4D (Define, Design, Develop and Disseminate). The results showed that the interactive learning website based on Google sites was highly valid for learning, with percentages of 96% from material experts, 96% from media experts and 97% from educational practitioners. The level of practicality of the websites was found to be 91%, as determined by student responses. This means that the interactive learning website based on Google sites is highly valid and feasible.